Catalyst material and air purification equipment
Through the combination of scaffold particles and catalytic particles, the problem of low activity of existing catalysts is solved, the catalytic performance and the on-the-action rate of air purification equipment are improved, more efficient VOCs decomposition is achieved, and air quality is improved.
Patent Information
- Application Number
- CN202310674140.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2024-12-17
AI Technical Summary
The activity of existing catalysts is low, resulting in low catalytic efficiency of air purification equipment when used, affecting the user experience.
A combination material of scaffold particles and catalytic particles is used, where the catalytic particles adhere to the surface of scaffold particles, and the particle size of the catalytic particles is smaller than that of scaffold particles. The catalytic particles are loaded with scaffold particles to avoid agglomeration, improve the exposure state and contact probability of catalytic particles, and enhance catalysis. performance.
It improves the activity and catalytic performance of catalyst materials, improves the on-activity rate and user experience of air purification equipment, effectively reduces indoor VOCs content, and improves air quality.
Smart Images

Figure CN119139912A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of air purification, and in particular to a catalyst material and air purification equipment. Background Art
[0002] In the related technologies, in order to control the indoor environmental pollution caused by VOCs (Volatile Organic Compounds), VOCs are usually catalytically decomposed based on catalytic degradation technology. However, in actual applications, it is found that the activity of most catalysts is low, resulting in relatively low catalytic efficiency, making it difficult for related purification equipment to take effect quickly when used, which in turn affects the user experience of the product. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the prior art or related art.
[0004] To this end, a first aspect of the present invention provides a catalyst material.
[0005] A second aspect of the present invention provides an air purification device.
[0006] In view of this, according to a first aspect of an embodiment of the present application, a catalyst material is proposed, comprising:
[0007] Scaffold particles;
[0008] A plurality of catalytic particles are attached to the surface of the support particles, and the particle size of the catalytic particles is smaller than the particle size of the support particles;
[0009] Among them, catalytic particles are used to catalyze the decomposition of VOCs.
[0010] In a feasible embodiment, the scaffold particles are zirconium oxide particles, aluminum oxide particles, silicon oxide particles, or titanium oxide particles.
[0011] In a feasible embodiment, the scaffold particles are spherical particles or block particles.
[0012] In a feasible embodiment, when the scaffold particles are spherical particles, the particle size thereof is greater than or equal to 5 μm and less than or equal to 30 μm;
[0013] When the scaffold particles are block particles, the particle size thereof is greater than or equal to 2 μm and less than or equal to 10 μm;
[0014] The particle size of the catalytic particles is greater than or equal to 100 nm and less than or equal to 800 nm.
[0015] In a feasible embodiment, the support particles include zirconium oxide particles, the catalytic particles include manganese oxide particles, and the manganese oxide particles are attached to the surface of the zirconium oxide particles.
[0016] In a feasible embodiment, the atomic number ratio of manganese element to zirconium element contained in the catalyst material is greater than or equal to 1 and less than or equal to 3.
[0017] In a feasible embodiment, the manganese content of the catalyst material is greater than or equal to 30 wt.% and less than or equal to 70 wt.%, and the zirconium content of the catalyst material is greater than or equal to 20 wt.% and less than or equal to 50 wt.%.
[0018] In a feasible embodiment, the valence forms of the manganese element in the catalyst material include trivalent manganese and tetravalent manganese, and the content of tetravalent manganese is greater than that of trivalent manganese.
[0019] In a feasible implementation, the ratio of the content of trivalent manganese to the content of tetravalent manganese is greater than or equal to 1.1 and less than or equal to 3.2.
[0020] In a feasible embodiment, in the XRD (Diffraction of X-Rays) diffraction pattern of the catalyst material,
[0021] In the range of diffraction angle greater than or equal to 28.0° and less than or equal to 28.2°,
[0022] The diffraction angle is greater than or equal to 31.3° and less than or equal to 31.5°.
[0023] In the range of diffraction angle greater than or equal to 34.0° and less than or equal to 34.3°,
[0024] In the range of diffraction angle greater than or equal to 50.0° and less than or equal to 50.2°,
[0025] The diffraction angle is greater than or equal to 36.8° and less than or equal to 37.0° and
[0026] In the range where the diffraction angle is greater than or equal to 65.7° and less than or equal to 65.9°,
[0027] There are diffraction peaks.
[0028] In a feasible embodiment, the catalytic temperature of the catalyst material is greater than or equal to 0°C and less than or equal to 50°C.
[0029] According to a second aspect of an embodiment of the present application, an air purification device is provided, comprising:
[0030] Filter;
[0031] The catalytic coating comprises the catalyst material as proposed in any one of the first aspects above, and is arranged on the filter screen.
[0032] In one feasible embodiment, the area of the filter screen provided with the catalyst material is greater than or equal to 95% of the total surface area of the filter screen; and / or
[0033] The porosity of the catalytic coating is greater than or equal to 15% and less than or equal to 35%.
[0034] Compared with the prior art, the present invention includes at least the following beneficial effects: the catalyst material provided in the embodiment of the present application includes a support particle and a plurality of catalytic particles, wherein the catalytic particles are attached to the surface of the support particle, and the particle size of the catalytic particles is smaller than the particle size of the support particle, and the catalytic particles can be used to catalyze the decomposition of VOCs to reduce the content of VOCs in the gas, achieve gas purification, and improve environmental quality. In practical applications, the catalyst material provided in the embodiment of the present application can be set in the filter of the air purification equipment, so that when the air in the environment where the air purification equipment is located flows through the aforementioned filter, the catalyst material can contact the aforementioned air and catalyze the decomposition of the VOCs contained in the aforementioned air to reduce the content of VOCs in the air, which is beneficial to reduce indoor environmental pollution and improve air quality; since the catalyst material provided in the embodiment of the present application The aforementioned support particles can be used to load catalytic particles, thereby avoiding agglomeration between catalytic particles and making the catalytic particles in a relatively good exposure state, which is beneficial to increasing the contact probability between the catalytic particles and the gas to be purified, thereby improving the activity of the catalyst material, and improving the catalytic performance and utilization rate of the catalyst material; and the particle size of the catalytic particles is smaller than the particle size of the support particles, which is convenient for using the support particles to load multiple catalytic particles at the same time, and allows multiple catalytic particles to be more dispersedly attached to the surface of the support particles, reducing the possibility of mutual shielding between adjacent catalytic particles, which is beneficial to further increase the probability of catalytic particles contacting the gas to be purified, improving the catalytic performance of the catalyst material, and thereby helping the catalyst material to more efficiently catalyze the decomposition of VOCs, increase the effectiveness rate of air purification equipment, and improve the user experience of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the exemplary embodiments below. The accompanying drawings are only for the purpose of illustrating exemplary embodiments and are not to be considered as limiting the present application. Also, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0036] Figure 1 A schematic structural diagram of a catalyst material of an embodiment provided in the present application;
[0037] Figure 2 A schematic structural diagram of a catalyst material of another embodiment provided in the present application;
[0038] Figure 3 A schematic XRD diffraction pattern of a catalyst material according to an embodiment of the present application.
[0039] in, Figure 1 and Figure 2 The corresponding relationship between the reference numerals and the component names is as follows:
[0040] 100 scaffold particles; 200 catalytic particles. DETAILED DESCRIPTION
[0041] The exemplary embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.
[0042] like Figures 1 to 3 As shown, according to the first aspect of an embodiment of the present application, a catalyst material is proposed, comprising: a support particle 100; a plurality of catalytic particles 200, attached to the surface of the support particle 100, wherein the particle size of the catalytic particle 200 is smaller than the particle size of the support particle 100; wherein the catalytic particle 200 is used to catalyze the decomposition of VOCs.
[0043] The catalyst material provided in the embodiment of the present application includes a support particle 100 and a plurality of catalytic particles 200, wherein the catalytic particles 200 are attached to the surface of the support particle 100, and the particle size of the catalytic particles 200 is smaller than the particle size of the support particle 100. The catalytic particles 200 can be used to catalyze the decomposition of VOCs to reduce the content of VOCs in the gas, achieve gas purification, and improve environmental quality.
[0044] It can be understood that, in actual applications, the catalyst material provided in the embodiments of the present application can be set in the filter of the air purification equipment, so that when the air in the environment in which the air purification equipment is located flows through the aforementioned filter, the catalyst material can contact the aforementioned air and catalyze the decomposition of VOCs contained in the aforementioned air to reduce the VOCs content in the air, which is beneficial to reduce indoor environmental pollution and improve air quality.
[0045] At the same time, since the catalyst material provided in the embodiment of the present application can utilize the aforementioned support particles 100 to load the catalytic particles 200, agglomeration between the catalytic particles 200 can be avoided, and the catalytic particles 200 can be in a relatively good exposure state, which is beneficial to increase the contact probability between the catalytic particles 200 and the gas to be purified, thereby improving the catalytic performance and utilization rate of the catalyst material.
[0046] It should be noted that, in practical applications, the aforementioned support particles 100 may be but are not limited to zirconium oxide particles, aluminum oxide particles, and silicon dioxide particles; the aforementioned catalytic particles 200 may be but are not limited to transition metal oxide particles, so as to improve the activity of the catalyst material and enhance the catalytic performance of the catalyst material. For example, the aforementioned transition metal oxide particles may be manganese oxide particles, thereby improving the specificity of the catalytic particle 200 material to formaldehyde, which is beneficial to reducing the formaldehyde content in the gas in practical applications.
[0047] Furthermore, the particle size of the catalytic particles 200 is smaller than that of the support particles 100, which makes it easier to use the support particles 100 to simultaneously load a plurality of catalytic particles 200, and enables the plurality of catalytic particles 200 to be more dispersedly attached to the surface of the support particles 100, thereby reducing the possibility of mutual shielding between adjacent catalytic particles 200, and is beneficial for further increasing the probability of the catalytic particles 200 contacting the gas to be purified, thereby improving the catalytic performance of the catalyst material, and thereby being beneficial for the catalyst material to more efficiently catalyze the decomposition of VOCs, thereby increasing the effectiveness rate of the air purification equipment, and improving the user experience of the product.
[0048] It should be noted that, in practical applications, in order to facilitate the use of the filter of the air purification equipment to load the aforementioned catalyst material, the catalyst material can be processed into smaller particles, so that the aforementioned support particles 100 can be micron-sized particles, and correspondingly, the aforementioned catalytic particles 200 can be nano-sized particles.
[0049] In some examples, the scaffold particle 100 is a porous structure.
[0050] In this technical solution, the support particle 100 can be a particle with a porous structure, so that the support particle 100 can have a relatively large specific surface area, which is beneficial to increase the contact range between the support particle 100 and the gas to be purified during use, and can also provide more attachment positions for the catalytic particles 200, which is beneficial to make the catalytic particles 200 more dispersedly distributed on the surface of the support particle 100. For example, a plurality of support particles 100 can be partially attached to the outer surface of the support particle 100, and part of the support particles 100 are located in the pores of the support particle 100. When part of the gas to be purified flows through the pores of the support particle 100, the VOCs contained in the gas to be purified can also be decomposed under the action of the catalytic particles 200 in the aforementioned pores. Based on the aforementioned settings, the utilization rate of the catalyst material and the catalytic efficiency can be further improved.
[0051] In some examples, the scaffold particles 100 are zirconium oxide particles, aluminum oxide particles, silicon oxide particles, or titanium oxide particles.
[0052] In this technical solution, the support particle 100 can be one of zirconium oxide particles, aluminum oxide particles, silicon oxide particles and titanium oxide particles, so that on the one hand, the support particle 100 can have good thermal stability, thereby ensuring the stability of the catalyst material in practical applications; on the other hand, it can also make the support particle 100 have a relatively rich pore structure, and then the support particle 100 can have a larger specific surface area, which is conducive to the attachment of the catalytic particle 200 to the support particle 100, thereby improving the loading capacity of the support particle 100.
[0053] like Figure 1 As shown, in some examples, the stent particles 100 are spherical particles; Figure 2 As shown, in some other examples, the stent particle 100 is a block particle.
[0054] In this technical solution, the support particles 100 can be spherical or blocky zirconium oxide particles, so that the support particles 100 can have a larger specific surface area, which makes it easier to use the support particles 100 to load the catalytic particles 200 and increase the exposure probability of the support particles 100 and the catalytic particles 200, thereby improving the catalytic efficiency and catalytic effect of the catalyst material in practical applications.
[0055] It should be noted that in actual applications, the catalyst material can be arranged in the form of a coating. For example, it can be bonded to the filter of the air purification equipment through an adhesive, so that part of the surface of the support particle 100 will contact the aforementioned adhesive and is difficult to be exposed to the air. Based on this situation, it can be understood that for support particles 100 of different structural forms, when the surface area required for bonding is the same, the support particles 100 with a larger specific surface area can also have a larger surface area exposed to the external environment. Furthermore, by setting the support particles 100 to be spherical particles or block particles, the exposure probability of the support particles 100 and the catalytic particles 200 can be increased, which is beneficial for the catalytic particles 200 to contact the gas to be purified, thereby further improving the catalytic effect of the catalyst material.
[0056] For example, the scaffold particles 100 may be spherical or blocky zirconium oxide particles, thereby facilitating further increasing the specific surface area of the scaffold particles 100 .
[0057] In some examples, when the support particle 100 is a spherical particle, its particle size is greater than or equal to 5 μm and less than or equal to 30 μm; when the support particle 100 is a block particle, its particle size is greater than or equal to 2 μm and less than or equal to 10 μm; the particle size of the catalytic particle 200 is greater than or equal to 100 nm and less than or equal to 800 nm.
[0058] In this technical solution, the particle size of the support particle 100 and the particle size of the catalytic particle 200 are constrained, wherein, in the case where the support particle 100 is a spherical particle, the particle size of the spherical particle is greater than or equal to 5 μm and less than or equal to 30 μm, and in the case where the support particle 100 is a block particle, the particle size of the block particle is greater than or equal to 2 μm and less than or equal to 10 μm. In combination with the above, it can be understood that the catalyst material can be in the form of smaller particles, and the particle size of the support particle 100 is greater than the particle size of the catalytic particle 200, so that the size of the support particle 100 will more directly determine the size of the catalyst material particles, and based on the above setting, on the one hand, the particle size of the catalyst material can be made smaller. Small, in practical applications, it is convenient to load the catalyst material more evenly and dispersedly on the filter of the air purification equipment, which is beneficial to improve the application convenience of the catalyst material and improve the utilization rate of the catalyst material; on the other hand, based on the particle size difference between the support particles 100 and the catalytic particles 200, it is also convenient to use the support particles 100 to load multiple catalytic particles 200 at the same time, and ensure that the multiple catalytic particles 200 can be in a relatively dispersed state, which is beneficial to further improve the contact probability between the catalytic particles 200 and the gas to be purified, and further improve the activity of the catalyst material, which is beneficial to enhance the catalytic performance and catalytic efficiency of the catalyst material, improve the starting rate of the air purification equipment, and improve the user experience of the product.
[0059] In some examples, the support particles 100 include zirconium oxide particles, and the catalytic particles 200 include manganese oxide particles, and the manganese oxide particles are attached to the surface of the zirconium oxide particles.
[0060] In this technical solution, the support particles 100 may include zirconium oxide particles, and the catalytic particles 200 may include manganese oxide particles. Accordingly, the zirconium oxide particles can be used to load manganese oxide particles. Based on the above-mentioned settings, on the one hand, the manganese oxide particles can be used to enhance the catalytic performance of the catalyst material and improve the catalytic efficiency of the catalyst material on formaldehyde, which is beneficial to reduce the formaldehyde content in the air in practical applications; on the other hand, it is also beneficial for the catalyst material to catalyze formaldehyde at room temperature, reduce the temperature requirements when the catalyst material is used, further improve the convenience of using the catalyst material, and help to improve the user experience of the product.
[0061] It is understandable that among the indoor environmental pollution problems caused by VOCs, formaldehyde pollution is particularly prominent. Based on the above-mentioned settings of the technical solution, the catalyst material's specificity to formaldehyde is enhanced, which is conducive to using the above-mentioned catalyst material in practical applications to promote the oxidation of formaldehyde in the air and decompose it into non-toxic carbon dioxide and water, which is beneficial to provide further protection for the health of users.
[0062] It can be understood that the aforementioned zirconium oxide particles can be spherical particles or block particles.
[0063] In some examples, the catalyst material includes a manganese element and a zirconium element having an atomic number ratio greater than or equal to 1 and less than or equal to 3.
[0064] In this technical solution, the ratio of the number of atoms of manganese and zirconium contained in the catalyst material is constrained. It can be understood that, when the support particles 100 include zirconium oxide particles and the catalytic particles 200 include manganese oxide particles, the aforementioned atomic number ratio can also reflect the ratio of the number of zirconium atoms contained in the support particles 100 to the number of manganese atoms contained in the catalytic particles 200. Therefore, when the particle size of the support particles 100 and the particle size of the catalytic particles 200 are certain, the limitation of the aforementioned atomic number ratio can, to a certain extent, constrain the quantitative relationship between the support particles 100 and the catalytic particles 200, which is conducive to the more dispersed distribution of multiple catalytic particles 200 on the surface of the support particles 100, so that the catalytic particles 200 are in a better exposure state, thereby improving the activity of the catalyst material and the catalytic performance of the catalyst material, which is conducive to more efficiently catalyzing the decomposition of VOCs such as formaldehyde in practical applications and improving the indoor environmental quality. In addition, when the catalyst material is provided in an air purification device, it can help to further improve the effectiveness rate of the aforementioned air purification device and enhance the user experience of the product.
[0065] In some examples, the catalyst material has a manganese content greater than or equal to 30 wt.% and less than or equal to 70 wt.%, and a zirconium content greater than or equal to 20 wt.% and less than or equal to 50 wt.%.
[0066] In this technical solution, the manganese content and zirconium content contained in the catalyst material are limited. It can be understood that when the support particles 100 include zirconium oxide particles and the catalytic particles 200 include manganese oxide particles, the aforementioned element content range can also reflect the number of zirconium oxide particles and manganese oxide particles in the catalyst material. Based on the aforementioned setting, on the one hand, when the particle size of the support particles 100 and the particle size of the catalytic particles 200 are certain, the limitation of the aforementioned element content range can constrain the quantitative relationship between the support particles 100 and the catalytic particles 200 to a certain extent, which is conducive to the more dispersed distribution of multiple catalytic particles 200 on the surface of the support particles 100, so that the catalytic particles 200 are in a better exposure state, thereby improving the activity of the catalyst material, enhancing the catalytic performance of the catalyst material, and being conducive to more efficient catalytic decomposition of VOCs such as formaldehyde in practical applications, and improving the indoor environmental quality; on the other hand, it can also ensure that the catalyst material contains more manganese oxide, which is conducive to providing further guarantee for the catalytic performance of the catalyst material and enhancing the catalytic efficiency of the catalyst material.
[0067] In some examples, the valence forms of the manganese element in the catalyst material include trivalent manganese and tetravalent manganese, and the content of tetravalent manganese is greater than that of trivalent manganese.
[0068] In this technical solution, the manganese element in the catalyst material can be in a mixed valence state, wherein the valence form of the manganese element can include trivalent manganese and tetravalent manganese, and the content of tetravalent manganese is higher than that of trivalent manganese. Based on the above-mentioned setting, on the one hand, the manganese oxide particles can have lattice defects, that is, oxygen vacancies, which is beneficial to promote the catalytic activity of the manganese oxide particles, further improve the catalytic performance and catalytic efficiency of the catalyst material, and facilitate more efficient catalytic decomposition of formaldehyde during use, thereby improving the indoor environmental quality; on the other hand, it can also avoid excessive oxygen vacancies in the manganese oxide particles, thereby providing a guarantee for the catalytic effect of the manganese oxide particles.
[0069] In some examples, the ratio of the content of trivalent manganese to the content of tetravalent manganese is greater than or equal to 1.1 and less than or equal to 3.2.
[0070] In this technical solution, the ratio of the content of trivalent manganese to the content of tetravalent manganese can be set to be greater than or equal to 1.1 and less than or equal to 3.2, so that on the one hand, it can further ensure that the manganese oxide particles have more oxygen vacancies, which is beneficial to improve the catalytic activity and catalytic efficiency of the manganese oxide particles, so that the catalyst material can catalyze the decomposition of formaldehyde more efficiently during use; on the other hand, it can avoid excessive defects in the manganese oxide particles, which is beneficial to improve the activity of the catalyst material while ensuring the catalytic effect of the catalyst material.
[0071] like Figure 3 As shown, in some examples, in the XRD diffraction pattern of the catalyst material, diffraction peaks exist in the range of diffraction angles greater than or equal to 28.0° and less than or equal to 28.2°, in the range of diffraction angles greater than or equal to 31.3° and less than or equal to 31.5°, in the range of diffraction angles greater than or equal to 34.0° and less than or equal to 34.3°, in the range of diffraction angles greater than or equal to 50.0° and less than or equal to 50.2°, in the range of diffraction angles greater than or equal to 36.8° and less than or equal to 37.0°, and in the range of diffraction angles greater than or equal to 65.7° and less than or equal to 65.9°.
[0072] In this technical solution, the crystal form of the catalyst material is limited. It can be understood that the aforementioned catalyst material can be a crystalline particle containing zirconium oxide particles and manganese oxide particles. The appearance position of the characteristic peak in the XRD diffraction pattern of the catalyst material can reflect the crystal form of the aforementioned catalyst material. Under the crystal form defined in this technical solution, the catalyst material can exhibit strong catalytic activity at room temperature, which is beneficial for the catalyst material to more efficiently catalyze the decomposition of formaldehyde during use and reduce the catalyst material's requirements for the catalytic environment temperature. When the catalyst material is set in an air purification device, it is also beneficial to further improve the onset rate of the air purification device, thereby improving the user experience of the product.
[0073] It should be noted that Figure 3 The stronger diffraction peaks that appear in the range of diffraction angles greater than or equal to 28.0° and less than or equal to 28.2°, the range of diffraction angles greater than or equal to 31.3° and less than or equal to 31.5°, the range of diffraction angles greater than or equal to 34.0° and less than or equal to 34.3°, and the range of diffraction angles greater than or equal to 50.0° and less than or equal to 50.2° are the diffraction peaks of zirconium oxide; the weaker diffraction peaks that appear in the range of diffraction angles greater than or equal to 36.8° and less than or equal to 37.0° and the range of diffraction angles greater than or equal to 65.7° and less than or equal to 65.9° are the diffraction peaks of manganese oxide.
[0074] For example, Figure 3As shown, in the XRD diffraction pattern of the catalyst material, diffraction peaks exist at diffraction angles equal to 28.1°, 31.4°, 34.1°, 50.1°, 36.9° and 65.8°. In this crystal form, the catalyst material exhibits strong catalytic activity and can have a relatively low catalytic temperature.
[0075] In some examples, the catalyst material has a catalytic temperature greater than or equal to 0°C and less than or equal to 50°C.
[0076] In this technical solution, the catalytic temperature of the catalyst material can be greater than or equal to 0°C and less than or equal to 50°C, so that the catalyst material can be catalyzed at room temperature in practical applications, and is therefore convenient for use in purification equipment and air supply equipment that do not have heating capabilities, thereby reducing the requirements of the catalyst material for use conditions and helping to expand the scope of use of the catalyst material.
[0077] It is understandable that the aforementioned catalytic temperature is also the lowest temperature at which the catalyst material can carry out the catalytic reaction, or the temperature at which the catalytic reaction begins to occur.
[0078] It is understandable that the catalytic temperature of the room temperature catalyst in the traditional technology is usually greater than or equal to 50°C and less than or equal to 80°C. Therefore, the catalyst material provided in the embodiment of the present application can further reduce the requirements for the catalytic environment temperature, so that the air purification effect can be achieved under normal temperature environment.
[0079] It is understandable that the aforementioned air supply equipment may be a fan, a blower, etc.
[0080] Illustratively, the catalytic temperature of the catalyst material may be less than or equal to 25°C.
[0081] It should be noted that, in practical applications, there may be multiple ways to prepare the catalyst material provided in the embodiments of the present application. Here, a method for preparing the aforementioned oxidant material is exemplarily provided. Taking the case where the support particles 100 include zirconium oxide particles and the catalytic particles 200 include manganese oxide particles as an example, the preparation method may include:
[0082] Step S1: Potassium permanganate or sodium permanganate is prepared into solution A, wherein the concentration of potassium permanganate or sodium permanganate in solution A is greater than or equal to 0.02 g / cm 3 And less than or equal to 0.06g / cm 3 It is understandable that, in the process of preparing the aforementioned solution A, in order to ensure that potassium permanganate or sodium permanganate is fully dissolved, stirring can be continued for a certain period of time, for example, stirring can be performed for 2 hours.
[0083] Step S2: Prepare zirconium oxychloride (ZrOCl2) into solution B, wherein the concentration of zirconium oxychloride in solution B is greater than or equal to 0.05 g / cm 3And less than or equal to 0.1g / cm 3 , and adding the aforementioned solution B to the aforementioned solution A to form a mixed solution C; it can be understood that in order to ensure that the aforementioned solution A and the aforementioned solution B are evenly mixed, the aforementioned solution B can be continuously stirred for 2 hours after being added to the aforementioned solution A, and through stirring, manganese oxide can be generated on the surface of the zirconium salt, which is beneficial to the subsequent use of zirconium oxide particles to load manganese oxide particles.
[0084] Step S3: slowly drop the reducing agent solution into the mixed solution C, and continue stirring for 4 hours to form a mixed solution D; it should be noted that the reducing agent may include at least one of formic acid, oleic acid, oxalic acid, oxalic acid, benzyl alcohol, methanol, ethanol, and ethylene glycol, that is, the reducing agent solution may contain both an acid reducing agent and an alcohol reducing agent. When the reducing agent solution contains both an acid reducing agent and an alcohol reducing agent, the molar ratio of the acid reducing agent to the alcohol reducing agent may be less than or equal to 0.5; illustratively, the reducing agent solution may contain oleic acid and benzyl alcohol, and the molar ratio of oleic acid to benzyl alcohol in the reducing agent solution is 1:3; and, under the action of the reducing agent solution, it is beneficial for the subsequently prepared catalyst material to have the crystal form given in the above scheme, thereby making the catalyst material have higher catalytic activity and catalytic efficiency.
[0085] Step S4: adding aqueous ammonia to the mixed solution D to form a mixed solution E, wherein the pH value of the mixed solution E is greater than or equal to 9 and less than or equal to 11; it can be understood that by adjusting the pH value of the solution, favorable reaction conditions can be provided for the components in the solution.
[0086] Step S5: continuously stirring the mixed solution E for 12 hours to obtain a reaction product;
[0087] Step S6: washing, filtering and drying the reaction product at 110° C. for 12 h;
[0088] Step S7: calcining the reaction product at 500° C. to obtain a catalyst material. It should be noted that by calcining the reaction product, the zirconium oxide particles can be formed into a porous structure, and defects in the manganese oxide particles can be created, so that the manganese oxide particles have oxygen vacancies, thereby further improving the catalytic activity and catalytic efficiency of the catalyst material.
[0089] As shown in Table 1, Table 1 lists the test results of the above catalyst materials. 3The test was carried out in a closed test cabin, in which an air purification device was arranged, and 100g of catalyst material was loaded on the filter of the aforementioned air purification device. During the test, 40mg of formaldehyde was injected into the aforementioned closed test cabin, and the formaldehyde was evenly distributed in the cabin space through the heating module and the circulating fan of the closed test cabin. Then the aforementioned air purification device was started and the changes in the formaldehyde concentration in the cabin were recorded. The aforementioned test cycle was carried out 100 times, and the formaldehyde removal rate of the air purification device when it was running for 30 minutes was statistically shown in Table 1. It can be seen that the air purification device, when loaded with the aforementioned catalyst material, can achieve a formaldehyde removal rate of more than 95% in 30 minutes, and has a high formaldehyde removal efficiency.
[0090] Number of tests 1 5 10 20 40 60 80 100 30min purification efficiency (%) 95.8 96.1 95.6 95.2 95.8 95.6 96 95.9
[0091] Table 1
[0092] According to a second aspect of an embodiment of the present application, an air purification device is proposed, comprising: a filter; a catalytic coating, comprising a catalyst material as proposed in any one of the first aspects above, arranged on the filter.
[0093] The air purification device provided in the embodiment of the present application includes a filter and a catalytic coating, wherein the catalytic coating includes a catalyst material as proposed in any one of the first aspects above, and the aforementioned catalytic coating can be arranged on the filter, so that the catalyst material can be arranged on the surface of the filter in the form of a coating. In practical applications, the aforementioned filter can be used to filter particulate matter, so that when the air purification device is running, the number of particulate matter carried by the air can be reduced, and the air quality can be improved. When the air flows through the aforementioned filter, the air can contact the catalyst material in the aforementioned catalytic coating, and then the air purification device can use the aforementioned catalyst material to catalyze the decomposition of VOCs contained in the air, so as to further reduce the content of toxic and harmful substances in the air and achieve further improvement in air quality.
[0094] At the same time, since the catalyst material provided in the embodiment of the present application can utilize the aforementioned support particles 100 to load the catalytic particles 200, agglomeration between the catalytic particles 200 can be avoided, and the catalytic particles 200 can be in a relatively good exposure state, which is beneficial to increase the contact probability between the catalytic particles 200 and the gas to be purified, thereby improving the catalytic performance and utilization rate of the catalyst material.
[0095] It should be noted that, in practical applications, the aforementioned support particles 100 may be but are not limited to zirconium oxide particles, aluminum oxide particles, and silicon dioxide particles; the aforementioned catalytic particles 200 may be but are not limited to transition metal oxide particles, so as to improve the activity of the catalyst material and enhance the catalytic performance of the catalyst material. For example, the aforementioned transition metal oxide particles may be manganese oxide particles, thereby improving the specificity of the catalytic particle 200 material to formaldehyde, which is beneficial to reducing the formaldehyde content in the gas in practical applications.
[0096] Furthermore, the particle size of the catalytic particles 200 is smaller than that of the support particles 100, which makes it easier to use the support particles 100 to simultaneously load a plurality of catalytic particles 200, and enables the plurality of catalytic particles 200 to be more dispersedly attached to the surface of the support particles 100, thereby reducing the possibility of mutual shielding between adjacent catalytic particles 200, and is beneficial for further increasing the probability of the catalytic particles 200 contacting the gas to be purified, thereby improving the catalytic performance of the catalyst material, and thereby being beneficial for the catalyst material to more efficiently catalyze the decomposition of VOCs, thereby increasing the effectiveness rate of the air purification equipment, and improving the user experience of the product.
[0097] It should be noted that, in practical applications, in order to facilitate the use of the filter of the air purification equipment to load the aforementioned catalyst material, the catalyst material can be processed into smaller particles, so that the aforementioned support particles 100 can be micron-sized particles, and correspondingly, the aforementioned catalytic particles 200 can be nano-sized particles.
[0098] It is understandable that the aforementioned catalytic coating may also include an adhesive, which is disposed on the aforementioned filter screen, through which the aforementioned catalyst material is bonded to the filter screen, and at least part of the support particles 100 and the catalytic particles 200 are exposed to the environment in which the filter screen is located.
[0099] In some examples, the area of the filter screen provided with catalyst material is greater than or equal to 95% of the total surface area of the filter screen; and / or the porosity of the catalytic coating is greater than or equal to 15% and less than or equal to 35%.
[0100] In this technical solution, the area of the filter screen provided with the catalyst material can be greater than or equal to 95% of the total surface area of the filter screen, thereby increasing the coverage rate of the filter screen surface by the aforementioned catalyst material, increasing the contact probability of the catalyst material with the gas to be purified, and further improving the purification performance of the air purification equipment.
[0101] It can be understood that the area of the filter screen provided with the catalyst material is the sum of the areas of the orthographic projections of the catalytic particles on the filter screen surface.
[0102] In this technical solution, the porosity of the catalytic coating can be greater than or equal to 15% and less than or equal to 35%, so that the catalytic coating can have a relatively rich pore structure, ensuring that the catalytic coating has a relatively high specific surface area, further increasing the contact probability between the catalyst material and the gas to be purified, and improving the purification performance of the air purification equipment.
[0103] It is understandable that the ratio of the area of the filter screen provided with the catalyst material to the total surface area of the filter screen, and the porosity of the catalytic coating can simultaneously adopt the aforementioned corresponding ranges to further improve the purification performance of the air purification device.
[0104] In some feasible examples, the air purification device may further include a housing and an air supply device, wherein the housing is formed with an air inlet, an air outlet and an air duct, and the air inlet and air outlet are both connected to the air duct; the filter may be arranged in the housing and located at the air inlet; the air supply device may be arranged in the air duct to supply air to the air outlet. Based on the above arrangement, the gas circulation efficiency of the air purification device can be improved, thereby further improving the purification efficiency of the air purification device.
[0105] It can be understood that the aforementioned air supply device can be a fan, and the catalytic temperature of the aforementioned catalyst material can be 25°C, so that the air purification equipment can also catalyze the decomposition of VOCs at normal temperature. Compared with the normal temperature catalyst in traditional technology, it can have smaller temperature condition restrictions and is suitable for more operating temperature environments.
[0106] In the present invention, the terms "first", "second", and "third" are used for descriptive purposes only and should not be understood as indicating or implying relative importance; the term "plurality" refers to two or more, unless otherwise clearly defined. The terms "installed", "connected", "connected", "fixed", etc. should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; "connected" can be a direct connection or an indirect connection through an intermediate medium. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0107] In the description of the present invention, it is necessary to understand that the directions or positional relationships indicated by terms such as “upper”, “lower”, “left”, “right”, “front” and “back” are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or unit referred to must have a specific direction, be constructed and operated in a specific orientation, and therefore, cannot be understood as a limitation on the present invention.
[0108] In the description of this specification, the description of the terms "one embodiment", "some embodiments", "specific embodiments", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0109] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A catalyst material, characterized in that include: Scaffold particles; A plurality of catalytic particles are attached to the surface of the support particles, and the particle size of the catalytic particles is smaller than the particle size of the support particles; Wherein, the catalytic particles are used to catalyze the decomposition of VOCs.
2. The catalyst material according to claim 1, characterized in that The scaffold particles are zirconium oxide particles, aluminum oxide particles, silicon oxide particles, or titanium oxide particles.
3. The catalyst material according to claim 1, characterized in that The scaffold particles are spherical particles or block particles.
4. The catalyst material according to claim 1, characterized in that When the scaffold particles are spherical particles, the particle size thereof is greater than or equal to 5 μm and less than or equal to 30 μm; When the scaffold particles are block particles, the particle size thereof is greater than or equal to 2 μm and less than or equal to 10 μm; The particle size of the catalytic particles is greater than or equal to 100 nm and less than or equal to 800 nm.
5. The catalyst material according to claim 1, characterized in that The support particles include zirconium oxide particles, and the catalytic particles include manganese oxide particles, wherein the manganese oxide particles are attached to surfaces of the zirconium oxide particles.
6. The catalyst material according to claim 5, characterized in that The catalyst material includes a manganese element and a zirconium element in an atomic number ratio greater than or equal to 1 and less than or equal to 3.
7. The catalyst material according to claim 4, characterized in that The manganese content of the catalyst material is greater than or equal to 30 wt.% and less than or equal to 70 wt.%, and the zirconium content of the catalyst material is greater than or equal to 20 wt.% and less than or equal to 50 wt.%.
8. The catalyst material according to any one of claims 5 to 7, characterized in that The valence forms of the manganese element in the catalyst material include trivalent manganese and tetravalent manganese, and the content of the tetravalent manganese is greater than that of the trivalent manganese.
9. The catalyst material according to claim 8, characterized in that The ratio of the content of trivalent manganese to the content of tetravalent manganese is greater than or equal to 1.1 and less than or equal to 3.
2.
10. The catalyst material according to any one of claims 5 to 7, characterized in that In the XRD diffraction pattern of the catalyst material, In the range of diffraction angle greater than or equal to 28.0° and less than or equal to 28.2°, The diffraction angle is greater than or equal to 31.3° and less than or equal to 31.5°. In the range of diffraction angle greater than or equal to 34.0° and less than or equal to 34.3°, In the range of diffraction angle greater than or equal to 50.0° and less than or equal to 50.2°, The diffraction angle is greater than or equal to 36.8° and less than or equal to 37.0° and In the range where the diffraction angle is greater than or equal to 65.7° and less than or equal to 65.9°, There are diffraction peaks.
11. The catalyst material according to claim 1, characterized in that The catalytic temperature of the catalyst material is greater than or equal to 0°C and less than or equal to 50°C.
12. An air purification device, characterized in that: include: Filter; The catalytic coating comprises the catalyst material according to any one of claims 1 to 11, and is disposed on the filter screen.
13. The air purification device according to claim 12, characterized in that: The area of the filter screen provided with the catalyst material is greater than or equal to 95% of the total surface area of the filter screen; and / or The porosity of the catalytic coating is greater than or equal to 15% and less than or equal to 35%.
